Time-optimal Earth–Mars transfer using nuclear electric propulsion - Su-Jin Choi; Morgan Choi (Nuclear Engineering and Technology)
This study focuses on the time-optimal end-to-end transfer trajectory between Earth and Mars using a low-thrust nuclear electric propulsion (NEP) system. The Korea Societies for Space Science and Nuclear have listed up various parameters for the Mars explorer, such as the initial mass, specific impulse, thrust of the NEP, and initial and final orbits of Earth and Mars, respectively. Based on this information, end-to-end transfer scenarios comprising the low Earth orbit to sphere of influence (SOI) of the Earth, Earth's SOI to Mars' SOI, and then to the low Mars orbit, were established. To investigate the relationship between flight time and required velocity increment (ΔV), various thrust levels (4–20 N) and direct optimal control problem were applied to the Earth–Mars transfer. As a result, the possibility of traveling to Mars from Earth using only NEP was confirmed. The flight time, burn time, and ΔV were estimated using the time-optimal problem, and the final masses at the Mars mission orbit (MMO) were obtained. When using a 4 N thrust level during the Earth–Mars transfer, the mass ratio of 46.45 % is required to reach the Mars mission orbit, whereas a 20 N thrust level can accomplish this with only 20.58 % mass ratio. Based on the simulation result, a total thrust level of 16 N, configuration of the thrusters, and lifetime requirement are recommended.